Regional Unemployment and Productivity in Europe and the US - Roberto Basile; Luca De Benedictis (European Regional Science Association (ERSA), 2004)
The existence and persistence of large spatial disparities in un-employment within national economies is a central issue in regional economics. Previous empirical analyses have largely disregarded the role of fundamentals. On the contrary in this paper we explore the link between labour productivity, international trade and regional un-employment differentials. We base our empirical analysis on the predictions of a simple General Oligopolistic Equilibrium effciency-wage trade model. Using semi parametric regression methods, controlling for industry-mix and labour force participation, we give evidence of a non linear negative relationship between labour productivity and regional unemployment, in the cases of European regions. Instead, no significant relationships between these variables have been found for the United States. Keywords: Productivity, Regional Unemployment, Oligopoly, Non parametrics. JEL Classification: C14, D50, F12, F16, J41, L13, R10.
Keywords: C14; D50; F12; F16; J41; L13; R10; 330; Productivity; Regional Unemployment; Oligopoly; Non parametrics